Incidence of neonatal hyperbilirubinemia in low, intermediate-low, and intermediate-high risk group infants - Ahmed Widiasta; Lelani Reniarti; Abdurachman Sukadi (Paediatrica Indonesiana, 2010)
Background Neonatal hyperbilirubinemia is commonly found in newborns. Assessment of the risk of hyperbilirubinemia and information on the average time of the occurrence of hyperbilirubinemia are important to prevent the development of severe hyperbilirubinemia.Objective To find out the incidence of and the time of the development of hyperbilirubinemia in healthy-term newborns.Method A cohort prospective study was done on healthy-term newborns born at Hasan Sadikin Hospital between November and December 2009. Subjects were divided into 4 groups of risk at discharged, based on Bhutani nonnogram. A serial bilirubin level measurement were perfonned within 6 days.Resu l ts One of 14 newborns at low risk group developed hyperbilirubinemia but did not need phototherapy. Six of 14 newborns at intermediate-low risk group developed hyperbilirubinemia, 2 of them needed phototherapy with total serum bilirubin level of 14.7 mg/dL at 57 hours and 19.8 mg/dL at111 hours. Nine of 15 newborns of intennediate-high risk group developed hyperbilirubinemia, 1 of them needed phototherapy with total serum bilirubin level of 16.6 mg/dL at 76 hours. There was no newborn cathegorized as high risk group in this study. The median time the occurrence of hyperbilirubinemia in intennediate-low and intennediate-high risk group was 140 hours and 82 hours, respectively. There was no significant difference in survival curve between intennediate-high and intennediate-low risk groups (95% CI 108.1 to 1 2 5.4).Conclusion The incidence of hyperbilirubinemia was not different between intennediate-low and intermediate-high risk babies.